Analisis Potensi Kekeringan Fisik Lahan Di Kabupaten Kulon Progo Tahun 2016 - Istiyani, Lilis, Drs. Yuli Priyana, M.Si (2017)
Physical Drought land is a natural phenomenon that occurs in the earth's surface as a result of factors that rocks can not store water and topographical factors. Physical Mapping drought land in Kulon Progo is necessary to determine the distribution of the potential regions of the physical drought land because of drought is always threatened when the dry season arrives. The method used is the analysis of GIS with tiered quantitative methods to produce maps of potential physical drought land. The parameter which are used in this research involve the utilization of the land, the slope, the landform, the drainage, and the available water capacity. The result of this research is a map of the level of potential physical drought land in Kulon Progo Regency which is divided into three classes, namely physical drought high land has an area of 254.42 km2 (43.53%), the potential physical drought land was 175.02 km2 (29, 94%), and potential low land physical dryness 155.05 km2 (26.53%) of the research area. Every insecurity level of dissemination in various districts in Kulon Progo Regency. The dominant factor that influence physical drought land in Kulon Progo Regency is landform.